Characterization of the pathogenesis and immune response to a highly virulent Edwardsiella tarda strain responsible for mass mortality in the hybrid snakehead (Channa maculate ♀ × Channa argus ♂). (September 2022) - Guo, Mengya; Zhang, Liwen; Ye, Jiaxin; He, Xiao; Cao, Pan; Zhou, Zicheng; Liu, Xiaodan
Abstract: Edwardsiella tarda is reported as the causative agent of the systemic disease Edwardsiellosis in fish, which lead to huge economic losses in aquaculture. The pathogenicity and immune response to a highly virulent E. tarda isolate responsible for mass mortality in hybrid snakehead were performed. After species identification, morphology and virulence gene detection of Edwardsiella isolated from hybrid snakehead, the pathogenicity of the strain and histopathological changes in infected fish were analyzed. The infected fish exhibited typical acute hemorrhagic symptoms and enlarged internal organs. Histopathology revealed that the liver, spleen, kidney and intestinal tissues of diseased fish exhibited marked inflammatory with vacuolar degeneration and cell necrosis. Subsequently, humoral immune factors such as superoxide dismutase, lysozyme and acid phosphatase activities were detected as serum indicators, and real-time quantitative PCR was used to investigate immune-related genes ( STAT1, HSP70, IgM, IL-6, IL-8, TRAF2, CD40, HLA-DMA and LCK ) expression patterns in liver, spleen and head kidney. The results showed that these enzyme activity indicators and immune-related gene expression were significantly activated compared with healthy fish. These data provide insight into the pathogenic mechanisms and host immune responses of E. tarda, which could be useful for the future prevention and treatment of Edwardsiellosis in fish. Highlights: The Edwardsiella tarda strain HZL1 was isolated and identified from diseased hybrid snakehead. Histopathological analysis of hybrid snakehead infected with E. tarda showed vacuolar degeneration and inflammatory. The activities of SOD, LZM and ACP in serum were significantly increased in hybrid snakehead infected with E. tarda. E. tarda infection triggers a broad defense response of various immune-related genes in hybrid snakehead.